Microstructure-property relationships in a gas diffusion layer (GDL) for Polymer Electrolyte Fuel Cells, Part II: pressure-induced water injection and liquid permeability. (1st July 2017) - Holzer, L.; Pecho, O.; Schumacher, J.; Marmet, Ph.; Büchi, F.N.; Lamibrac, A.; Münch, B.
Highlights: Liquid distribution in GDL is investigated with injection tomography experiments. Anisotropy of liquid breakthrough is triggered by short-range effect in through-plane. Quantitative 3D analysis reveals microstructure limitations for liquid permeability. Relative permeability (κrel )-curves are 'S-shaped' due to distinct microstructure effects. Macroscopic descriptions for κrel from literature are not capable to capture the 'S-shape'. Abstract: The performance of polymer electrolyte fuel cells (PEFC) strongly depends on a controlled water management within the porous layers. For this purpose we investigate liquid water transport in a commercial gas diffusion layer (SGL 25BA) on the pore scale. X-ray tomography experiments combined with pressure-induced water injection provide 3D images of the liquid water distribution inside the GDL at incremental pressure steps between 0 and 100 mbar. The breakthrough behavior of the liquid phase is highly anisotropic. In through-plane (tp) direction first bubble points appear at the outlet plane already at 5 mbar and the 'breakthrough' then evolves continuously over an extended pressure range up to > 30 mbar. For in-plane (ip) direction the breakthrough is discontinuous and takes place at 27 mbar. Simulations of the intrusion process reveal that the different breakthrough behaviors are mainly triggered by different ip- and tp-transport distances. Short tp-transport distances through the thin gas diffusion layer (ca. 100 μm) are responsible for the characteristic continuous tp-breakthrough behavior, which is thus attributed to a so-called short-range effect. Dedicated methods for 3D-image analysis adapted to fibrous GDL microstructures were presented in part I. With these methods we quantify all microstructure characteristics that are relevant for liquid permeability. These characteristics of pore and liquid phases include size distributions of bulges and bottlenecks, connectivity, effective volume fractions, geodesic tortuosity, constrictivity and hydraulic radius. Quantitative relationships are established between these microstructure characteristics and the liquid permeability, which provide a better understanding of the underlying microstructure limitations for injection and liquid transport. For the in-plane direction the liquid permeability is limited to roughly a similar extent by tortuosity, constrictivity and effective volume fraction. In contrast, for through-plane direction relatively low volume fractions of the liquid phase put stronger limitations to the liquid permeability than tortuosity, constrictivity and hydraulic radius. The curves for relative permeability vs. saturation (and vs. capillary pressure, respectively) achieved from 3D-analysis reveal complex but characteristic (reproducible) shapes with concave, linear and convex segments. The shape of these segments can be attributed to distinct microstructure effects. In contrast, the conventional macroscopic descriptions from literature cannot capture these complex shapes and the underlying microstructure effects. Future investigations with different GDL materials are necessary in order to understand whether these complex shapes for the relative permeability represent a general feature of gas diffusion layers or if they are specific to the investigated SGL material.